EP.TU.581Cholecysto-colonic fistula – A rare complication of gallstone. (28th October 2021) - Loganathan, Santhosh; Singh, Amal; O'Connor, Adam; Antony, Martin
Abstract: We present a 90year old male patient presenting to the emergency department with complaints of PR bleed for a month with no associated abdominal pain. He described that the blood was mixed with stools and dark in colour. He has a significant past medical history with multiple comorbidities. The patient is known to have gallstones and had ERCP with sphincterotomy in 2017 as a definitive treatment, as he wasn't a fit candidate for surgical intervention. On clinical examination, his abdomen was soft and non-tender and per rectal examination showed stools mixed with the blood but no active bleeding or fresh blood. His haemoglobin was 72 g/L, inflammatory markers were significantly elevated with deranged liver enzymes and normal bilirubin. The medical team were involved in the management of this patient because of pneumonia and extensive medical issues. A gastroscopy was performed as there was a suspicion of UGI bleed, which was normal. Given a deranged liver function and there was a suspicion of biliary sepsis patient had MRCP and Computed tomography of the abdomen which confirmed that there is haematoma in the gallbladder with gas in the biliary tree, with possible cholecysto-colonic fistula, with a large gall stone (2.7cm lamellated structure within rectum) in the rectum. As the patient was not a surgical candidate decision was made to manage him conservatively with antibiotics under medical care. The cholecysto-colonic fistula is a rare complication of gallstone disease, and very few cases have been reported in the literature.